ANALISIS KINERJA PEMASOK PADA PT. BIMANDIRI AGRO SEDAYA DALAM AKTIVITAS PENGADAAN BROKOLI (Brassica oleracea var. italica L.) - Ayu Nurhusni; Kuswarini Kusno (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Supplier performance plays an important role in ensuring the availability of supply goods that will affect the company's performance. PT. Bimandiri Agro Sedaya is a distributor of high quality fresh vegetables that relies on suppliers to procure all vegetables. One of the vegetable commodities with the highest demand and continues to increase from the company is broccoli, but the company's service level in meeting customer demand has actually decreased due to lack of supply from suppliers. This study aims to describe the purchasing process in the procurement of broccoli, as well as to determine the performance ranking of the best broccoli suppliers at PT. Bimandiri Agro Sedaya. The design applied in this research is qualitative and quantitative with case study research techniques. The first objective is achieved by conducting descriptive analysis, while the second goal is achieved by using the Analytical Hierarchy Process (AHP) method. Based on the results of the study, the purchasing process in the procurement of broccoli at PT. Bimandiri Agro Sedaya consists of six stages, namely making quantity estimates, ordering to suppliers, receiving orders from customers, sending broccoli by suppliers, receiving and checking broccoli, and payments to suppliers. Furthermore, the first rank of broccoli supplier with the best performance is Mr. Yayang (50.9%), the second rank is PTA (20.7%), the third rank is IDF (14.7%), and the last rank is Mr. Ayi Ilham (13,7%).